The importance of the paint cross section to the examination of painted decorations in historic interiors. 'Press brocate' relief on stone (Bulletin KNOB, 2000)
In order to examine the paint layers on architectural structures or decorations, tiny paint samples are prepared into paint cross sections for microscopic analysis. This technique has been developed within the field of conservation of paintings and polychromed sculpture. By studying paint cross sections under a stereomicroscope conclusions concerning the painting technique and painting materials can be drawn: the composition and build up of grounds, paint layers, metal leaf, glazes or varnish layers can be analysed.By using ultraviolet radiation some binding media has been recognized for some years now because of their characteristic fluorescence. Based on their specific colour and morphology many pigments can be determined. The meaning and importance of this microscopic technique for the examination of figurative paintings and historic paint schemes in buildings is recognised for some years now.In the Great or Our Ladies Church in Breda and the Pieters Church in Leiden remnants of imitation gold brocate or so-called 'press brocate' relief are found on the columns in the interior. The condition and technical composition of these decorations were investigated by the Stichting Restauratie Atelier Limburg.Only by examining cross sections it was possible to determine the original appearance of the fragmented decorations. Indeed the technique resembled that of press brocate, so often encountered on medieval sculptures and early panel paintings. Brocate patterns were engraved for instance in a lead plate. In this mould a thin leave of tin was pressed. The resulting relief was fixed by a wax coating on the back. The front could be gilded or painted with a golden glaze and subsequently with coloured glazes.In the early 16th century the columns in both churches must have been adorned with beautiful tapestries functioning as a background for statues of saints. Also in the Cellebroeders chapel in Maastricht, small black stars could be identified as decorations in a press brocate technique by the examination of cross sections. Originally, the stars must have looked like golden stars in the dark, brightly sparkling and reflecting the candlelight.